Committing to justice: An analysis of criminal law reforms in Chile - (:unkn) unknown (My University, 2016)
From 1997 to 2001, the Chilean government enacted laws to transform its criminal justice system from one using a closed and secretive inquisitorial-type process to one employing a more open and transparent adversarial process.These criminal procedure reforms significantly changed the roles of lower court judges, prosecutors and public defenders and provided defendants and victimswith broader individual rights. Despite its commitment to criminal law reforms, during the implementation period of these reforms, the government remained lackluster in its commitment to a more open and transparent justice systemwhen it related to more politicized cases. This paper explores the connection between the government’s commitment to lower level criminal law reforms and its policy switch in dealing with more politicized cases.